Security and Reliability Analysis of the Power Splitting-Based Relaying in Wireless Sensors Network - Tran, Minh; Tu, Lam-Thanh; Minh, Bui Vu; Nguyen, Quang-Sang; Rejfek, Luboš; Lee, Byung Moo (MDPI, 2024)
This paper studies the security and reliability of the power splitting (PS)-based relaying in the Internet of Things (IoT) networks with the help of a jammer. Based on the considered system model, we derive outage probability (OP) and intercept probability (IP) under two distinguished schemes, namely, the static PS relaying (SPSR) scheme and the dynamic PS relaying (DPSR) scheme. More precisely, the PS ratio of the former is a constant number, while the latter is optimally adjusted in order to minimize the OP and counts only on the channel gain of the second hop. Numerical results are provided to not only verify the accuracy of the proposed mathematical framework but also identify the trends of both OP and IP with respect to several important parameters. Our findings unveil that the OP and IP have contradictory behavior with respect to the transmit power and number of sources. Moreover, the performance of the DPSR scheme is superior to that of the SPSR scheme.
Analýza bezpečnosti a spolehlivosti relé založeného na rozdělení výkonu v síti bezdrátových senzorů
Keywords: intercept probability; Internet of Things; outage probability; performance analysis; relaying networks; pravděpodobnost zachycení; Internet věcí; pravděpodobnost výpadku; analýza výkonnosti; Předávací sítě